PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KESEJAHTERAAN PSIKOLOGIS AWAK KAPAL DALAM ERA DIGITALISASI PELAYARAN - Samekto, Agus Aji (UNIMAR AMNI Semarang, 2024)
This study aims to examine the effect of transformational leadership on the psychological well-being of seafarers, as well as to analyze the moderating role of transformational leadership in the relationship between technostress, a consequence of maritime digitalization, and psychological well-being. Along with the acceleration of digital transformation in the maritime industry, seafarers face new psychological challenges in addition to existing traditional work stressors. This study adopts a quantitative approach with a cross-sectional survey design involving Indonesian seafarers from various types of vessels. Data were collected using three main instruments: the Multifactor Leadership Questionnaire (MLQ) to measure transformational leadership, Ryff's Scales of Psychological Well-being to measure psychological well-being, and the Techno-Stress Scale to measure the level of technology-induced stress. The results of hierarchical multiple regression analysis show that transformational leadership has a positive and significant effect on the psychological well-being of seafarers. Furthermore, the moderation analysis indicates that transformational leadership significantly mitigates the negative impact of technostress on psychological well-being. These findings provide strong practical implications for the shipping industry, emphasizing the urgency of developing transformational leadership competencies for ship officers as a key strategy to maintain the mental health and resilience of seafarers in facing the complexities of the digital era.